Activation model for various punching shear reinforcement types in flat slabs and column bases optimized for design. (15th December 2021) - Schmidt, Philipp; Pleim, Michel; Bielak, Jan; Hegger, Josef
Highlights: The activation of punching reinforcement in flat slabs and column bases is analyzed. The mechanical background of activation for next Eurocode 2 (prEC2) is explained. An extended activation formula considering bond and anchorage is derived for prEC2. Different types of shear reinforcement are considered on a uniform basis. Focus is on transformation from a mechanical model to a simplified design formula. The proposed activation formula is validated by systematic punching test results. Abstract: Various types of punching shear reinforcement have been developed during the past decades to increase the punching capacity and ductility of slab-column connections. Due to diverse geometries and thus varying anchorage conditions, the effectiveness of these elements contributing to total punching resistance can differ significantly. Generally, the degree of activation of shear reinforcement can be described by contributions of anchorage and of bond. Yet, most of current punching design provisions follow a simplified, empirical approach. Despite its mechanical background, the punching design according to the next generation of Eurocode 2 still does not consider the effect of better anchorage of, for example, double headed studs compared to simple stirrups. In this paper, an extended activation formula for flat slabs as well as column bases is proposed as refinement for the next generation of Eurocode 2. This unifying approach considers different anchorage categories and thus enables more progressive design results. After discussing the background of possible activation scenarios, the effects of bond and anchorage in cracked concrete and the kinematic deformation behavior of slabs subjected to punching are identified as governing constraints. The major focus is on the transformation process from mechanical considerations to a simplified design formula to ensure practical applicability.